UPAYA PENGEMBANGAN UMKM MAKANAN OLAHAN DI KABUPATEN KARANGANYAR - Bekti Wahyu Utami; Choirul Anam; Widiyanto Widiyanto (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2014)
Through this service activity is expected both in terms of MSME5 partners then there will be an increase in the production of better product quality and management side of business management are expected to meet market demand by increasing marketing reach To overcome the problems faced by the MSMEs team devotion offers several methods of problem solving , among others : a ) introduction of appropriate technology in the form of spinner tool, b) introduction of appropriate technology tools such as vacuum sealer, c ) recognition and processing training to improve the quality of food product and d) a field trip as on effort to diversify the product.This activity is expected to only a stimulus for MSMEs partners that required active participation in sustainability activities, partner SMEs proactive response during activity is an early indicator that this devotion is a participatory empowerment is not actually even foster charity/dependence for the MSMEs.